Analisis Strategi Pemasaran Dalam Meningkatkan Jumlah Konsumen dI Makassar Cofee House (MCH) - Halik, Johannes Baptista; Nurlia, Nurlia; Latiep, Ifah Finatry (Master of Management Study Program, Universitas Kristen Indonesia Paulus, 2023)
This research aims to find out what strategies can be implemented at the Makassar Coffee House in Makassar City. The data collection method in this research uses field research by applying two methods, namely interviews and observation. The data analysis methods used are Internal Factor Matrix (IFAS), External Factor Matrix (EFAS), SWOT Matrix and SPACE Matrix. The research results show that in the IFAS Factors there are five strength factors and five weakness factors in the Makassar Coffee House (MCH) with a total IFAS Factor score of 1.00. In the EFAS factors there are five opportunity factors and three threat factors with a total score of 1.95. In the SWOT Matrix there are two S-O strategies, namely maintaining the taste, especially of coffee drinks and maintaining free delivery costs for delivery orders, S-T strategy, namely providing good service to customers and balancing product prices and raw material prices, W-O strategy, namely creating a new menu, especially coffee. and food as well as collaborating with local offices and providing special offers, W-T's strategy is to increase promotions. In the SPACE Matrix, the results are in quadrant I, so the suitable strategy to carry out is the S-O strategy.